Surface-EMG analysis for the lower limb muscle characteristics of top level women speed skater in short distance - Huang, D.; Liu, L.; Xie, C. (Academic Journal of Humanities & Social Sciences, 2020)
Purpose: To insight into thelower limb muscle characteristics of top level speed skater in short distance, in terms of iEMG, excitation intensity, and activation modality. Methods: Three female word champion speedskaters participated in this study. EMG data was collected in the second straight by ME6000 when gliding in a standard speed skating rink. Results: tibialis anterior and quadriceps muscle are the main work muscles in supporting phase; The excitation intensity of tibialis anterior and biceps femoral is bigger in flexion phase, while others (gastrocnemius lateralis , vastus medialis, vastus lateralis, rectus femoris, semitendinosus muscle and gluteus muscle) are bigger in extension phase; the onset of tibialis anterior is first, followed by the vastus medialis, vastus lateralis and biceps femoral; the offset of tibialis anterior is first, then the vastus medialis, vastus lateralis and gastrocnemius lateralis at the time of off-ice. Conclusion: The main work muscles is consistent in elite athletes; muscle activation modality is regular in the same technique in elite athletes; Elite athletes' technique is very stable. Short -track speed skaters should put more punch on gastrocnemius strength training when switch to speed skate.